ANALISIS PERGERAKAN DAN AKUMULASI COULOMB STRESS GEMPA UTAMA LOMBOK SELAMA TAHUN 2018 DAN PENGARUHNYA TERHADAP AKTIVITAS GUNUNG RINJANI - Lasroha Marulitua Panjaitan; Erlangga Ibrahim Fattah; Cahli Suhendi; Rizki Wulandari; Hana Yudi Perkasa (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Mechanically, earthquakes can be triggered by changes in static and dynamic stress. In terms of static stress change, it occurs when earthquake energy is released which then changes the stress conditions around the fault (for example at the end of the fault). The process of changing static stress in an area will cause seismic activity to occur in the surrounding area and in other areas with a great distance. The amount of change in Coulomb Failure stress (∆CFS) is quantifiable and has proven to be a powerful tool in explaining the movement and accumulation of stress caused by the mainshock and its aftershock. This study was conducted to calculate the distribution of stress changes due to the main Lombok earthquake (Mw≥6) during 2018 and its effect on Mount Rinjani activity, using the Coulomb 3.3 software. The earthquake data used were taken from the earthquake catalog of Global Centroid Moment Tensor (GCMT), International Seismological Center (ISC) and United States Geological Survey (USGS). The lateral difference in the value of ∆CFS shows the movement of energy from the main earthquake that triggered another earthquake as shown by the aftershock data. The results of this analysis of the movement and accumulation of ∆CFS will be used to identify the correlation with the activity of Mount Rinjani.